Integrative Cell Type-Specific Multi-Omics Approaches Reveal Impaired Programs of Glial Cell Differentiation in Mouse Culture Models of DM1 - González-Barriga, Anchel; Lallemant, Louison; Dincã, Diana M.; Braz, Sandra O.; Polvèche, Hélène; Magneron, Paul; Pionneau, Cédric; Huguet-Lachon, Aline; Claude, Jean-Baptiste; Chhuon, Cerina; Guerrera, Ida Chiara; Bourgeois, Cyril F.; et al. (Frontiers in Cellular Neuroscience, 2021)
Myotonic dystrophy type 1 (DM1) is a neuromuscular disorder caused by a non-coding CTG repeat expansion in the DMPK gene. This mutation generates a toxic CUG RNA that interferes with the RNA processing of target genes in multiple tissues. Despite debilitating neurological impairment, the pathophysiological cascade of molecular and cellular events in the central nervous system has been less extensively characterized than the molecular pathogenesis of muscle/cardiac dysfunction. Particularly, the contribution of different cell types to DM1 brain disease is not clearly understood. We first used transcriptomics to compare the impact of expanded CUG RNA on the transcriptome of primary neurons, astrocytes and oligodendrocytes derived from DMSXL mice, a transgenic model of DM1. RNA sequencing revealed more frequent expression and splicing changes in glia than neuronal cells. In particular, primary DMSXL oligodendrocytes showed the highest number of transcripts differentially expressed, while DMSXL astrocytes displayed the most severe splicing dysregulation. Interestingly, the expression and splicing defects of DMSXL glia recreated molecular signatures suggestive of impaired cell differentiation: while DMSXL oligodendrocytes failed to upregulate a subset of genes that are naturally activated during the oligodendroglia differentiation, a significant proportion of missplicing events in DMSXL oligodendrocytes and astrocytes increased the expression of RNA isoforms typical of precursor cell stages. Together these data suggest that expanded CUG RNA in glial cells affects preferentially differentiation-regulated molecular events. This hypothesis was corroborated by gene ontology (GO) analyses, which revealed an enrichment for biological processes and cellular components with critical roles during cell differentiation. Finally, we combined exon ontology with phosphoproteomics and cell imaging to explore the functional impact of CUG-associated spliceopathy on downstream protein metabolism. Changes in phosphorylation, protein isoform expression and intracellular localization in DMSXL astrocytes demonstrate the far-reaching impact of the DM1 repeat expansion on cell metabolism. Our multi-omics approaches provide insight into the mechanisms of CUG RNA toxicity in the CNS with cell type resolution, and support the priority for future research on non-neuronal mechanisms and proteomic changes in DM1 brain disease.